2023
DOI: 10.3389/fncir.2023.1007755
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding neuronal diversity and neural circuit complexity across different brain regions using single-cell sequencing

Abstract: Neural circuits are characterized as interconnecting neuron networks connected by synapses. Some kinds of gene expression and/or functional changes of neurons and synaptic connections may result in aberrant neural circuits, which has been recognized as one crucial pathological mechanism for the onset of many neurological diseases. Gradual advances in single-cell sequencing approaches with strong technological advantages, as exemplified by high throughput and increased resolution for live cells, have enabled it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 124 publications
0
3
0
Order By: Relevance
“…Notably, analysis of cell type-specific spontaneous activity has revealed that precise temporal patterns, rather than synchrony per se , better reflect neuronal identity. Recent studies using single-cell RNA sequencing have uncovered distinct cell types at an unprecedented resolution ( Saunders et al, 2018 ; Zeisel et al, 2018 ; Piwecka et al, 2023 ; Xing et al, 2023 ; Zhang et al, 2023 ). A key challenge moving forward will be to investigate whether cell type-specific temporal activity patterns are also present in other brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, analysis of cell type-specific spontaneous activity has revealed that precise temporal patterns, rather than synchrony per se , better reflect neuronal identity. Recent studies using single-cell RNA sequencing have uncovered distinct cell types at an unprecedented resolution ( Saunders et al, 2018 ; Zeisel et al, 2018 ; Piwecka et al, 2023 ; Xing et al, 2023 ; Zhang et al, 2023 ). A key challenge moving forward will be to investigate whether cell type-specific temporal activity patterns are also present in other brain regions.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid advancement of single‐cell transcriptomic studies in the nervous system has led to the discovery of an increasing number of cell types and their corresponding marker genes (Armand et al, 2021; Xing et al, 2023; Yuste et al, 2020). This wealth of information can be harnessed to design a greater variety of drivers for combinatorial targeting strategies.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…These networks are complex and diverse; their make-up consists of various neuron types with regards to function and morphology. For example, networks can be composed of different ratios of excitatory and inhibitory subtypes of neurons that secrete different types of neurotransmitters, and they can be distinct depending on the brain region (Hanganu-Opatz et al, 2021;Xing et al, 2023). Neural networks are often defined by synchronous and oscillatory neuron activity that can vary in brain states and are dependent on synaptic connectivity within or across regions (Whittington et al, 2018).…”
Section: Astrocyte Coordination Of Neural Network Activity Within Org...mentioning
confidence: 99%